Study of indications for cardiac device implantation and utilisation in Fabry cardiomyopathy. Issue 23 (24th August 2019) - Vijapurapu, Ravi; Geberhiwot, Tarekegn; Jovanovic, Ana; Baig, Shanat; Nordin, Sabrina; Kozor, Rebecca; Leyva, Francisco; Kotecha, Dipak; Wheeldon, Nigel; Deegan, Patrick; Rusk, Rosemary A; Moon, James C; et al.
Abstract : Background: Fabry disease is a treatable X-linked condition leading to progressive cardiomyopathy, arrhythmia and premature death. Atrial and ventricular arrhythmias contribute significantly to adverse prognosis; however, guidance to determine which patients require cardiovascular implantable electronic devices (CIEDs) is sparse. We aimed to evaluate indications for implantation practice in the UK and quantify device utilisation. Methods: In this retrospective study, we included demographic, clinical and imaging data from patients in four of the largest UK Fabry centres. Ninety patients with Fabry disease were identified with CIEDs implanted between June 2001 and February 2018 (FD-CIED group). To investigate differences in clinical and imaging markers between those with and without devices, these patients were compared with 276 patients without a CIED (FD-control). Results: In the FD-CIED group, 92% of patients with permanent pacemakers but only 28% with implantable cardioverter-defibrillators had a class 1 indication for implantation. A further 44% of patients had defibrillators inserted for primary prevention outside of current guidance. The burden of arrhythmia requiring treatment in the FD-CIED group was high (asymptomatic atrial fibrillation: 29%; non-sustained ventricular tachycardia requiring medical therapy alone: 26%; sustained ventricular tachycardia needing anti-tachycardia pacing/defibrillation: 28%). Those with devices were older, had greater LV mass, more scar tissue and larger atrial size. Conclusions: Arrhythmias are common in Fabry patients. Those with cardiac devices had high rates of atrial fibrillation requiring anticoagulation and ventricular arrhythmia needing device treatment. These are as high as those in hypertrophic cardiomyopathy, supporting the need for Fabry-specific indications for device implantation.